Analisis Penerapan Pembelajaran Billingual dengan Model PBL Berbantuan Platform ABCya Pada Materi Bentuk Geometri Bangun Ruang - Margawati, Puput Tri; Surya, Firman Adi; Magfiroh, Anis; Nadia, Amalia Salma; Hardiyatni, Shanti; Hardiyanti, Shinta; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the implementation of bilingual learning (Indonesian-English) using the Problem-Based Learning (PBL) model assisted by the ABCya digital platform in teaching 3D geometry to elementary students. Through qualitative library research, five key studies (2020-2024) were analyzed, focusing on how this integrated approach affects conceptual understanding, language acquisition, and learning motivation. Findings reveal that: (1) PBL’s problem-solving framework enhances spatial reasoning while naturally embedding bilingual terminology; (2) ABCya’s gamified interface significantly increases engagement through interactive 3D shape visualization; and (3) the bilingual approach strengthens both mathematical and linguistic competencies when balanced appropriately. The study highlights the importance of teacher competency in bilingual pedagogy and the need for supportive learning environments. These results align with constructivist principles and multimedia learning theory, demonstrating how technology-enhanced PBL can transform abstract geometric concepts into tangible bilingual learning experiences.